Factor Authentication for Banking System by using Android based Smart Phones (International Journal of Engineering and Computer Science, 2015)
: This is an Android based Smartphone Application for mobile payments or electronic wallet services. This work includes themobile payment device and the paying client. This two device featuring 3 factor authentication and ad hoc network makes the transactionmore secure as compared to the traditional credit card payment. The 3 factor authentication feature includes the IMEI(InternationalMobile Equipment Identity) authentication, facial bio-metric authentication and user authentication. The facial bio metric authenticationis used to authenticate the user so that the unauthorized person should not be able to perform the transaction.